HPLC METHOD DEVELOPMENT AND VALIDATION OF LERCANIDIPINE HCL AND ATENOLOL, CHARACTERIZATION OF ITS DEGRADANTS BY LC-MS/MS - RAO, P. T. S. R. K. PRASADA (International Journal of Applied Pharmaceutics, 2022)
Objective: An assay method was developed and validated for the simultaneous estimation of Lercanipine HCl and atenolol using RP-HPLC. Methods: An effective chromatographic separation was achieved using waters symmetry C18 column of dimensions 150x4.6 mm, 3.5 μm, as a stationary phase. 0.1 percent ortho phosphoric acid and acetonitrile in 50:50 v/v was used as a mobile process with a rate of flow 1 ml/min and UV detection was carried out at 230 nm, respectively. Isocratic chromatography at ambient temperature was performed. Results: Lercanidipine HCl and atenolol were separated by a running time of around 8 min. at 2.925 min. and 6.482 min. Respectively. By injecting the norm six times, device suitability parameters were studied and the outcomes were well under the acceptance criteria. The linearity analysis was performed at levels ranging from 10% to 150% and the R2 value was found to be 0.999. Conclusion: Assay method validation was performed by using the marketed formulation and found to be within the limit. Degradation tests were conducted and the degradants were characterized by using LC-MS/MS.